Capsule Formulation of Ethanolic Extract of Pasak Bumi (Eurycoma Longifolia Jack.,) and its Effect on Human Health Vital Signs - Laela Hayu Nurani; Eka Kumalasari; Abdul Rohman; Sitarina Widyarini (Faculty of Pharmacy, Universitas Gadjah Mada, 2017)
Pasak bumi (Eurycoma longifolia) has the potential to be developed as antihypertensive, antipyretic, aphrodisiacs and health supplements. The use of E. longifolia as a traditional medicine needs to be pursued in the form of more effective and appropriate formulation. The capsule preparations are easy to make and cancover the bitter taste of E. longifolia. Clinical trials in this study use design pre-post treatment in healthy humans. Subjects used were male - healthy men and healthy women who met inclusion criteria and were subjected with formulated capsule for 14 days. The study resulted capsule formula comprising of the ethanolic extract of E. longifolia 300 mg, vivapur 101 300 mg, 58 mg maydis starch, aerosil 3%, talc 2%, and Mg stearate 1%. The results showed that the capsule of E. longifolia did not affect the value of heart rate, respiration rate, body temperature and weight (P > 0.05), based on paired t-test, but they causes a decrease in blood pressure of healthy human. The ethanol extract of E. longifolia caused vasodilation of blood vessels that can be used in antihypertensive therapy.